PATTERNS OF DRUG ABUSE AND PREVALENCE OF DEPENDENCE IN SURABAYA CITY - Gresika, Ade Marda; Setiadi, Antonius Adji Prayitno (HEARTY, 2025)
The negative effects of improper use of drugs have also been increasingly reported. Physical effects experienced by drug users include heart problems, disturbances in the brain's work, disorders of the nervous system, infection with dangerous infectious diseases such as HIV / AIDS and others. Meanwhile, the psychological or mental effects that will be experienced by abusers are attitude and mental changes. The purpose of this study was to obtain a percentage of grouping individual characteristics, patterns of abuse and prevalence of drug dependence. The type of research used is descriptive method with quantitative data collection and presentation. The research design used was an ex-post facto research design. In the ex-post facto study there were no control groups or pre-test activities. The sampling technique that will be used in this study is purposive sampling technique. Data collection methods used are questionnaire and interview methods. This study was dominated by men (83.78%), the highest age range was at the age of 16 25 years (37.84%), the latest education was dominated by high school graduates / equivalent (54.05%), dominated by entrepreneurs (51.35%), with part time work time (43.24%), living together with the nuclear family (86.49%). Environmental factors are the most factors which cause respondents to use drugs (86.50%). The methadone maintenance program is only known to heroin users.